Pandangan eksistensialisme terhadap pendidikan karakter kedisiplinan dalam pembelajaran pendidikan kewarganegaraan - Kharisma Romadhon Madon; Maemonah; Fildza Malahati; Sri Atin; Irfan Irfan; Ummi Atya Nurjanna (Universitas Kanjuruhan Malang, 2023)
The purpose of this study is to define the analysis of the character of student discipline in Civics subjects from an existentialist perspective. This research method uses qualitative analysis with a case study approach, namely research that is designed to provide explanations from researchers and retrieve information generated in the field through direct communication between researchers and informants. The object of this research was carried out at MI Darussalam Plaosan. The informants involved were fourth grade educators/teachers at Madrasah Ibtidaiyah Darussalam Plaosan, Klaten, Central Java. The results of the study show that the character of student discipline in Civics subjects in the view of existentialism can be described in four concepts including: (1) self-potential, (2) exploring self-ability, (3) self-awareness, and (4) self-discipline